Immunohistochemical Analysis of Somatostatin Receptors in Endometriosis Tissue Samples: A Retrospective Study. (July 2019) - Fastrez, Maxime; Marchisello, Camille; Rassy, Marc; Rozenberg, Serge; Sirtaine, Nicolas
Abstract : Three types of endometriosis are described: superficial peritoneal endometriosis (SPE), ovarian endometrioma (OMA), and deep infiltrating endometriosis (DIE). The expression of somatostatin receptors (SSTR1, 2, and 5) in human endometrial tissue and its ectopic form has been previously studied and may be different in each type of endometriosis. The aim of this study was to assess the immunohistochemical expression of SSTR1, 2, and 5 in tissue samples of SPE, OMA, and DIE. We performed a retrospective analysis in the pathology department database. Patients aged <50 yr and diagnosed with endometriosis have been identified and sorted into 3 groups according to their endometriosis type: SPE, OMA, and DIE. For each selected patient, formalin-fixed paraffin-embedded blocks were retrieved in order to make new sections to be incubated with polyclonal rabbit antibodies anti-SSTR1, 2, and 5. Receptor status was considered as positive on the sections when >50% of the cells showed immunostaining. Seventy-six patients were included in the analysis. SSTR1 and 5 were expressed in 95.4% and 77.2% of SPE, respectively, in 95.8% and 83.3% of OMA, respectively, and in 100% and 80% of DIE, respectively. There was no significant difference between SPE, OMA, and DIE with regard to the SSTR1 ( P =0.5) and SSTR5 ( P =0.9) expression. We observed a significant difference between SPE (9.0%), OMA (16.6%), and DIE (63.3%) with regard to SSTR2 expression ( P <0.05). The present study identifies 2 different immunohistochemical patterns of endometriosis lesions with regard to their SSTR expression: SSTR1+/SSTR2−/SSTR5+ for SPE and OMA, and SSTR1+/SSTR2+/SSTR5+ for DIE.